Development of Higher Order Thinking Skills-Based Multiple Choice Test Items Using Quizizz Application to Measure the Cognitive Abilities of Early Childhood Students in the Early Beginning Classes - Tuti Hidayati; Rivo Panji Yudha (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to determine the development of Higher Order Thinking Skills (HOTS)-based multiple-choice question instruments through Quizizz application to measure the cognitive abilities of early childhood students in the early grades. The method used in this study is the research and development ADDIE method. The results of this study show that the developed HOTS instrument using Quizizz meets the validity criteria based on validity tests. The results of content validity test by subject matter experts indicate 90% validity with a highly valid category, while the media experts' validation results show 83% validity with a highly valid category. The practicality questionnaire validation results from the students indicate 85% validity with a highly valid category. The results of construct validity test state that each item has a calculated r-value higher than the table r-value, indicating its validity and suitability for use. The reliability test yields a value of 0.799, which falls under the high reliability category with a range of 0.600-0.800. The difficulty level test results, with an average of 0.73, indicate that the questions are easy, demonstrating good quality difficulty levels. The item discrimination test results show an average of 0.432, indicating good discriminatory ability. The practicality test results from the students show 89% practicality with a highly practical category. Based on the test results of the students' abilities after being given the questions, it can be concluded that out of the 97 students who answered the 20 HOTS multiple-choice questions, 55 students had an excellent level of ability, 10 students had a good level of ability, 27 students had an average level of ability, and 5 students had a very poor level of ability. Thus, the average score of the 97 students is 71%, falling under the good category.